Philosophies Teori Konsep Keperawatan Jean Watson Caring - Rinezia Rinza Farizal; Irna Nursanti (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Background: Jean Watson nurse theorist and nursing professor known for the “Philosophy and Theory of Transpersonal Care.” She has also written many books, including Nursing: The Philosophy and Science of Caring. Watson's studies of caring have been integrated into education and patient care in nursing schools and healthcare facilities around the world. Jean Watson was born Margaret Jean Harmon and raised in Welch, West Virginia, Watson is known for seeing the unified science of caring, examining the role of the nurse through the lens of a worldview of harmony, belonging, and connection. In caring theory, values, knowledge and caring practices are integrated with the healing process from within and the patient's life experiences, thus requiring the art of healing-care and a framework called carative factors. These factors are complementary, but different from curative factors. Curative is developed by doctors, while carative is developed by nurses. Caring behavior can determine the moral values ??of nurses. In addition, caring behavior in nursing care can determine the level of client satisfaction in receiving health services. It can be said that caring is a wholehearted attitude or behavior given by a nurse to a client with a sense of care, attention and attention to the patient's emotions to create a therapeutic relationship. This causes patients to feel comfortable, safe and relieved because of the reduction in stress they feel due to suffering from an illness.